PROBLEMS OF INFORMATION AND ANALYTICAL SUPPORT OF CONTEMPORARY STRATEGIC MANAGEMENT - M. A. Rodionov (Научный вестник МГТУ ГА, 2016)
The problematic aspects have been considered with regard to the information and analytical support of a strategic decision making in the modern management. The role and place are clarified in relation to a process of elaboration and making a management decision in strategic planning. The existing approaches are analyzed regarding the estimating of regularities in the course and outcome of strategic processes. The strategic forecasting matters have been studied as well as a decision maker`s attitude to the risks.